Statement by the Managing Director on the Work Program of the Executive Board : Executive Board Meeting. (Policy Papers; Policy Paper ;, 2017)
This Work Program (WP) translates the policy priorities and strategic directions laid out in the Spring 2017 Global Policy Agenda (GPA) and the International Monetary and Financial Committee (IMFC) Communique into an Executive Board agenda for the next twelve months. The Managing Director's GPA, welcomed by the IMFC, called on members to continue using supportive policies based on a three-pronged approach to sustain the recovery, to work together within the multilateral framework toward strong and more balanced growth, and to provide economic opportunities for all. It outlined how the Fund would support the membership by promoting efforts to sustain the recovery, lift productivity and increase resilience, and by promoting sustainable policies toward a more inclusive global economy, while facilitating multilateral solutions to global challenges. Where the work extends beyond traditional areas, the WP will focus on macro-relevant issues that are systemically important or relevant for many countries and amenable to change through economic policies.